Gender and disability among older adults in north and south India: Differences associated with coresidence and marriage - MANISHA SENGUPTA & EMILY M. AGREE (Journal of Cross-Cultural Gerontology 17: 313-336, 2002., 2002)
Women in most settings are more likely than men to experience as well as report poor health and functional disabilities. Studies in the economically advanced countries (as in the US) have also shown an association between gender, marital status and health and disability. However, there is very little information about gender differentials in disability among the elderly in developing countries, especially those in South Asia. Also, little is known about the association between gender, marital status, coresidence with sons, and disability among older adults in these countries. This study uses data from the National Family Health Survey conducted in India in 1991-1992 to assess the gender disparities in functional health among persons 55 years and older and to compare the situation in the northern and southern parts of the country. Using logistic regression analysis, this study examines the relation between marital status, living arrangements and functional status of older adults in the states of Uttar Pradesh and Haryana in the north and Kerala and Tamil Nadu in the south. The results confirm a female disadvantage in physical impairments in the northern states, although these differences are not significant in the south. Marital status and coresidence with sons is associated with impairments and these associations show interesting interactions.